Welding of high entropy alloys: Progresses, challenges and perspectives. (August 2021) - Li, Junchen; Meng, Xiangchen; Wan, Long; Huang, Yongxian
Abstract: High entropy alloys (HEAs) and HEAs-related materials have developed rapidly over the last decade, and the key issues have gradually emerged when the welding of HEAs are required. Here, we provide a critical review on the state-of-the-art for the welding of HEAs-related materials, aiming to address the weldability of HEAs under the compositional diversity, different initial states, welding processes and parameters, joint configurations and service conditions. The recent progresses and challenges about fusion-based welding, solid-state welding and diffusion reaction-based welding of HEAs are reviewed comprehensively, considering the joints' microstructures, mechanical properties and functional performances. Additionally, HEAs fillers have exhibited great potentials in suppressing the formation of intermetallic phases, tailoring the weld components and improving the joint properties. The development tendency on the welding of HEAs is proposed, including establishing the criteria between HEAs-systems and the corresponding welding processes, employing the materials genome engineering strategy in HEAs designing and welding simulation, and exploring HEAs joints with multi-functional and high value-added applications.